Studi Literatur tentang STEM (Sains, Technologi, Engineering, and Mathematics) dalam Pembelajaran Biologi - Subchan Adi; Ospa Pea Yuanita Meishanti (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2023)
ABSTRACT Abstract: This STEM approach is an approach that refers to the four components of science, namely knowledge, technology, engineering, and mathematics. This STEM later in research will be reviewed and modified into biology subjects. The purpose of this research is to analyze the application of the STEM approach to biology learning. This research uses the study literature method which has a concept with data collection and data sources used are secondary data, which come from journals and scientific papers totaling at least 20 sources (journals/articles). The results that the researchers found were that the STEM approach to biology learning could be integrated with various learning models and appropriate materials and could improve student learning outcomes, students' critical thinking skills, students' scientific literacy, students' creativity, students' ability to think scientifically. Keywords: STEM Approach, Biology Learning. ABSTRAK Abstrak: Pendekatan STEM ini adalah pendekatan yang merujuk kepada empat komponen ilmu pengetahuan, yaitu pengetahuan, teknologi, teknik, dan matematika. STEM ini nantinya pada penelitan yan akan di kaji dimodifikasikan ke dalam mata pelajaran biologi. Tujuan dari penelitian ini adalah untuk menganalisis penerapan pendekatan STEM pada pembelajaran biologi. Penelitian ini menggunakan metode study literature yang mempunyai konsep dengan pengumpulan data dan sumber-sumber data yang digunakan merupakan data sekunder, yang berasal dari jurnal dan karya tulis ilmiah yang berjumlah minimal 20 sumber (jurnal/artikel). Adapun hasil yang peneliti temukan adalah pendekatan STEM pada pembelajaran biologi dapat diintegrasikan dengan berbagai model pembelajaran dan materi yang sesuai serta dapat meningkatkan hasil belajar siswa, keterampilan berpikir kritis siswa, literasi sains siswa, kreativitas siswa, kemampuan berpikir ilmiah. Kata kunci: Pendekatan STEM, Pembelajaran Biologi